The Stress management program - Michaels, Jerome; Petrie Method, Inc. (Englewood Cliffs, NJ : Prentice Hall Audio, Business & Professional Division, 1990)
Presents an interactive program designed to help the listener eliminate anger more easily and deal with everyday situations through the use of hypnosis.
Title from narration: The stress management hypnosis program.
In container (25 cm.)
Workbook prepared by and cassettes narrated by Jerome Michaels.
Keywords: Stress management; Anger -- Prevention; Hypnotism -- Therapeutic use